From Grain to Pixel The Archival Life of Film in Transition - Fossati, Giovanna (Framing Film, 2011)
Film is in a state of rapid change, with the transition from analog to digital profoundly affecting not just filmmaking and distribution, but also the theoretical conceptualization of the medium film and the practice of film archiving. New forms of digital archives are being developed that make use of participatory media to provide a more open form of access than any traditional archive has offered before. Film archives are thus faced with new questions and challenges. From Grain to Pixel attempts to bridge the fields of film archiving and academic research, by addressing the discourse on film ontology and analysing how it affects the role of film archives. Fossati proposes a new theoretization of film archival practice as the starting point for a renewed dialogue between film scholars and film archivists.